Role of ascorbic acid in counteracting ferric nitrilotriacetate-induced nephrotoxicity in rats. (11th September 2013) - Ansar, S.; Iqbal, M.
Abstract: Context : Ascorbic acid (AA) is a naturally occurring organic compound with antioxidant properties. It is necessary for normal growth and development, and has been shown to protect against tissue toxicity and oxidative stress. Objective : The protective effect of AA against nephrotoxicity induced in albino rats by ferric nitrilotriacetate (Fe-NTA) was evaluated. Materials and methods : Male albino rats of Wistar strain (4–6 weeks old) weighing 125–150 g were used in this study. Animals were given a single dose of Fe-NTA (9 mg/kg body weight, intraperitoneal) after a week of treatment with AA (1 and 2 mg/animal/day). Results : Fe-NTA treatment enhanced microsomal lipid peroxidation (LPO) and hydrogen peroxide (H2 O2 ) generation to 1.7- to 2.2-fold, glutathione (GSH) levels were decreased by two-fold and the activities of GSH metabolizing enzymes decreased to a range of 2.2- to 2.5-fold in renal tissue. These changes were reversed significantly in animals receiving pretreatment of AA. Treatment of rats with AA prior to the treatment with Fe-NTA decreased microsomal LPO and H2 O2 generation to 124 and 172%, and also resulted in the recovery of reduced levels of GSH, GSH-metabolizing enzymes to almost 92% at the higher dose level of AA. Discussion and conclusion : AA protects against Fe-NTA-induced nephrotoxicity and renal damage. AA has a beneficial impact on Fe-NTA-induced toxicity due to its scavenging and antioxidant effect in albino rats.